Awake Intubation in Patient with Superoanterior Mediastinal Mass and Superior Vena Cava Syndrome (SVCS): A Case Report - Ery Oktadiputra; I Putu Fajar Narakusuma; Tjokorda Gde Agung Senapathi (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2025)
Superior vena cava syndrome (SVCS) with airway compression is challenging in anesthesia management. We report the case of a 69-year-old man with a superoanterior mediastinal mass and grade 3 SVCS who underwent Video-Assisted Thoracoscopic Surgery (VATS) with awake intubation using a double lumen tube (DLT) and videolaryngoscope. Awake intubation was chosen as the safest anesthesia technique where patients still breathe spontaneously without experiencing the effects of deep sedation. The combination of 4% lidocaine nebulization, oropharyngeal lidocaine spray, and dexmedetomidine infusion (0.5 μg/kg bolus over 10 minutes followed by 0.3-0.6 μg/kg/hour during surgery) in this patient, successfully maintained spontaneous ventilation without hemodynamic complications. The use of nebulized lidocaine, lidocaine spray, and dexmedetomidine as intubation facilities showed excellent effectiveness by maintaining the patient's spontaneous breathing, increasing the pain threshold, suppressing the nausea-vomiting reflex, and providing comfort in the form of mild sedation during awake intubation. This approach emphasizes the importance of topical anesthesia and selective sedation in high-risk patients with airway difficulties.